2021
DOI: 10.5755/j01.itc.50.4.29464
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cryptography Algorithms Implemented in Android Mobile Application

Abstract: This paper evaluates the performances of numerous encryption algorithms on mobile devices running the Android operating system. The primary objective of our research was to measure and compare the relative performances of tested algorithm implementations (Data Encryption Standard (DES), 3DES, Advanced Encryption Standard (AES), ChaCha20, Blowfish, and Rivest Cipher 4 (RC4)) on the Android platform. The algorithms were compared in terms of CPU utilization by measuring the time required to encrypt and decrypt va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…ERSA encryption times also showed a proportional relationship between data size and encryption time [17]. This made their encryption times predictable, deterministic, and patterned which confirms the work of Masram et al [39] and [38,[40][41][42][43][44][45]. The use of longer keys ensures higher security but results in higher CPU utilization when encryption time is dependent on data size (O (N)) [46].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…ERSA encryption times also showed a proportional relationship between data size and encryption time [17]. This made their encryption times predictable, deterministic, and patterned which confirms the work of Masram et al [39] and [38,[40][41][42][43][44][45]. The use of longer keys ensures higher security but results in higher CPU utilization when encryption time is dependent on data size (O (N)) [46].…”
Section: Discussionsupporting
confidence: 72%
“…From these discussions, it could be concluded that data size is proportional to the decryption time for Salsa20, Chaca20, and ERSA as indicated in Table 2. This makes their trend of decryption time deterministic, predictable, and linear which is supported by the works of [44,51]. With a linear trend of decryption time, hackers can predict, intercept and modify data [52].…”
Section: Plos Onementioning
confidence: 94%
“…However, they are performed independently and not concurrently in a single step. To understand these overheads, we tap on the work of Alen et al, [105] which analyses and evaluates the performance of several cryptographic algorithms on file size up to 10 megabytes using mobile devices with varied hardware specifications running different versions of the Android operating system. Using AES-GCM 128 bits key size on 10 kilobytes, it takes just 11ms.…”
Section: Complexitymentioning
confidence: 99%